Keratins as markers that distinguish normal and tumor-derived mammary epithelial cells. - Trask, D K (1990)
Keratin 5 (K5) mRNA and protein are shown to be expressed in normal mammary epithelial cells in culture and are absent from tumor-derived cell lines. To extend these findings, the full complements of keratins in normal, immortalized, and tumor cells were compared. It is shown here that normal cells produce keratins K5, K6, K7, K14, and K17, whereas tumor cells produce mainly keratins K8, K18, and K19. In immortalized cells, which are preneoplastic or partially transformed, the levels of K5 mRNA and protein are lower than in normal cells, whereas the amount of K18 is increased. Thus, K5 is an important marker in the tumorigenic process, distinguishing normal from tumor cells, and decreased K5 expression correlates with tumorigenic progression.